Tunnel-soil-structure interaction mechanisms in a metallic arch bridge. (May 2022) - Faherty, Ruth; Acikgoz, Sinan; Wong, Eugene K.L.; Hewitt, Peter; Viggiani, Giulia M.B.
Highlights: Tunnel-bridge-soil interaction problem is examined. 2D finite element models interacting with non-linear soil formulated parametrically. Model predictions compared with monitoring data for a real bridge. Influence of expansion joints and bearings on interaction quantified. Plausible range of soil conditions and tunnelling scenarios investigated. Abstract: Tunnel excavation causes ground movements that can affect the serviceability of surface structures, including bridges. These often feature compliant joints between structural components, such as bearings and expansion joints, which reduce stresses under operational loads. However, joints affect the stiffness of the structure and may impact soil-structure interaction mechanisms in unexpected ways. To develop an improved understanding of these mechanisms, a two-dimensional parametric modelling approach is formulated in this study, which enables rapid generation of model geometry to investigate the influence of tunnelling on arch bridges. Elastic Euler beam elements are used to model the arch, deck and spandrel elements while concentrated zero-length springs are used to idealise bridge joints. The soil is modelled using non-linear Winkler springs, distributed at the embedded sections and base of the piers. Tunnelling-induced greenfield displacements are applied to the soil elements to simulate soil-structure interaction. First, an application of the numerical model to simulate the response of a steel arch railway bridge affected by Thames Tideway tunnels is presented. This case study indicates good agreement between the proposed models and field monitoring data and highlights the key role of bridge joints on tunnel-soil-structure interaction mechanisms. To explore these aspects further, numerical simulations are carried out for superstructure arrangements with and without bridge joints, various soil conditions and tunnel eccentricities. The influence of these aspects on bridge structural integrity is quantified using the force and strain distribution in the structural elements, and is summarised with the utilisation ratio. Due consideration is also given to bridge serviceability by investigating salient displacement measures, such as roller bearing travel and deck elevation changes.